2001
DOI: 10.1089/089277901750161935
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study of Transurethral Resection of the Prostate and Combined Transurethral Resection and Vaporization of the Prostate as a Therapeutic Alternative in Men with Benign Prostatic Hyperplasia

Abstract: From our preliminary experience, vapor-cut seems to give results comparable to those of TURP. Because there is almost no bleeding during vapor-cut, the procedure is performed under excellent visibility, which permits more rapid and effective resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…132,202,203 Two of the three studies reported no statistically significant differences between TUVRP and TURP (Appendix 8.8 , Table 76), whereas in the third study, reporting means and standard deviations, the mean difference was 0.30 ( Figure …”
Section: At 3 Monthsmentioning
confidence: 99%
See 4 more Smart Citations
“…132,202,203 Two of the three studies reported no statistically significant differences between TUVRP and TURP (Appendix 8.8 , Table 76), whereas in the third study, reporting means and standard deviations, the mean difference was 0.30 ( Figure …”
Section: At 3 Monthsmentioning
confidence: 99%
“…Point estimates and measures of variability were presented in 88% of the studies, although in three studies it was unclear whether means or medians were used as the point estimate measure. 134,152,153 The dropout rate was unlikely to cause bias in 12 studies 124,138,150,[154][155][156][157][158][159][160][161][162] but this information was unclear in 74 (85%) of the studies. Only 16 studies (18%) stated that an intention to treat analysis was performed; however, this seems questionable in 11 of these studies 57,70,125,130,136,139,145,154,[163][164][165] as they failed to include the total number of participants in each arm in the subsequent follow-up assessments and an additional study stated that patients failing to complete the treatment or failing to return for follow-up were substituted.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations